Design for the Development of a Kampung Siaga Bencana Through Capacity Building in Participatory Planning in Cintaasih Village, Gekbrong Subdistrict, Cianjur Regency, West Java, Indonesia - Sriseptayana, Fenny; Kuswanda, Dede; Mildawati, Milly (International Journal of Science and Society, 2025)
The Disaster-Resilient Village (Kampung Siaga Bencana/KSB) is a community-based disaster risk reduction initiative designed to protect communities from disaster risks by strengthening local preparedness. This study aims to develop a KSB design through capacity building in participatory planning in Cintaasih Village, Gekbrong Subdistrict, Cianjur Regency. The research employed a qualitative approach using the Participatory Action Research (PAR) method. The participants consisted of eight purposively selected individuals, including members of the KSB team in Cintaasih Village, village officials, and representatives from the Cianjur District Social Office. Data collection techniques included in-depth interviews, observation, document analysis, and focus group discussions (FGDs), and were analyzed using the Miles and Huberman interactive model. The findings revealed that the initial KSB design was still predominantly top-down and had not fully empowered the local community. The KSB team in Cintaasih lacked the capacity to independently formulate action plans due to limited skills in locally needs based planning. The final design improved the previous process by integrating several capacity building components, including team building training, best practice sharing on community-level disaster response, education on community participation, simulation and training of the three stages of the Technology of Participation (ToP) method, and dissemination of planning guidelines. The model was also supported by technical assistance in activity reporting and a monitoring and evaluation mechanism coordinated by the Cianjur District Social Office. The implementation of this design proved effective in enhancing the knowledge, skills, and initiative of the KSB team. The participatory process fostered a sense of ownership over the action plan and helped build stronger and more sustainable internal mechanisms. The study recommends follow-up research to expand the model’s utility and replicability, enabling the participatory design to be tested, validated, and further developed into an adaptive or standardized model.